Mathematics, Physics, and Plants: A Case Study of Fibonacci Series - Janina Marciak-Kozlowska; Miroslaw Kozlowski (European Scientific Journal, ESJ, 2016)
There were eras where an educated man could only live up to his standard if he was a poet and a philosopher at the same time, or an experimental or a mathematical researcher. I argue that it is time to return back and look into the areas of physics, mathematics, and botany from different perspective of Fibonacci series